Effectiveness of Breast Ultrasound for Breast Cancer Screening : A Systematic Review - P. Pangaribuan, Hotman (Indonesian Health Journal, 2024)
Breast cancer is the most common cancer in Indonesia and has the highest mortality rate in women. Nowadays, the primary prevention is not clear yet to prevent the breast cancer. Secondary prevention with radiological modality is the only option to decrease the mortality of breast cancer. This study aims to identify ultrasound effectiveness and accuracy as a screening modality for early detection of breast cancer. Methods: A systematic review was analyzed using PRISMA without a meta-analysis method on articles published in 2014-2024. Articles searches were conducted using PubMed, Science Direct, and Google Scholar Database. Result: Based on the search results, seven eligible articles met the criteria for analysis. We found consistent evidence in 5 studies that breast cancer screening using ultrasound has high sensitivity (range sensitivity 68.9%-100%) and accuracy (range accuracy 0.687-0.999) compared to mammography alone. Breast ultrasound specificity is lower than mammography, ranging from 22% to 99.9%. The positive predictive value ranges from 4.3%-70%, and the negative predictive value of breast ultrasound ranges from 61.2%-100%. Conclusion: Breast Ultrasound can be an option as a breast cancer screening modality, especially in young women with dense breasts. It can be used in health facilities where mammography is unavailable.